Production of clean hydrogen via nuclear and solar energy by optimization - Sarılmaz, Gurur Furkan (My University, 2022)
Günümüz dünyasının en büyük sorunu enerjidir. Hidrojen bu sorunun cevabı olarak öne çıkmaktadır. Sıfır emisyonlu yöntemlerle yakıt üretimi günümüzde bir ihtiyaca dönüşmüştür. Söz konusu sıfır emisyon ile enerji üretimi olduğunda, yenilenebilir enerji kaynakları önemli bir rol oynar. Yenilenebilir enerji kaynaklarından üretilen elektrik, bir nükleer santrale kıyasla çoğunlukla dalgalıdır. Bu dezavantaj, sabit miktarda ve hava durumlarından bağımsız enerji üretebilen nükleer santralle birleştirildiğinde ortadan kaldırılabilir. Talepten fazla elektrik enerjisi üretimi söz konusu olduğunda, NHES de, elektrik üretimine ek olarak elektroliz ile temiz hidrojen üretilebilir. Bu çalışmada, nükleer enerji ile birlikte solar enerjinin kullanıldığı bir nükleer hibrit enerji sistemi analiz edilir. Elektrik ve hidrojen çıktısı olan bu hibrit sistemin, toplam kar bakımından optimizasyonu ele alınır. NHES de yer alan üç ana alt sistemin (nükleer reaktör, photovoltaic ve elektroliz ünitelerinin), teknolojik olarak hazırlık seviyeleri hakkında bilgi verir.

The biggest problem of today's world is energy. Hydrogen stands out as the answer to this question. Fuel production with zero-emission methods has become a necessity today. When it comes to energy generation with zero emissions, renewable energy sources play an important role. Electricity generated from renewable energy sources are mostly fluctuating compared to a nuclear power plant. This disadvantage can be eliminated when combined with a nuclear power plant, which can produce a constant amount of energy independent of weather conditions. In the case of electricity generation in excess of demand, clean hydrogen can be produced by electrolysis in addition to electricity generation in NHES. In this study, a nuclear hybrid energy system in which solar energy is used together with nuclear energy is analyzed. Optimization of this hybrid system, which has electricity and hydrogen output, in terms of total profit is discussed. Information is given about the technological readiness levels of the three main subsystems (nuclear reactor, photovoltaic and electrolysis units) in NHES.
Keywords: güneş enerjisi; hibrit enerji sistemleri Nuclear power plant; Hidrojen üretimi; Hybrid energy systems; Hydrogen production; Makine mühendisliği; Mechanical engineering; Nükleer santral; Solar systems